Metropolitan planning for immigrant integration - Emília Malcata Rebelo (2004)
This paper, which is based on the research project Urban Planning for Immigrant Integration presents the main results of a research project currently being lead in the Territorial and Urban Planning Section of the Faculty of Engineering of Porto University (Portugal). Its purpose is to establish a set of analytical tools in order to support municipal power decision-making processes related to immigrant integration, and it is applied, as a case study, to the Porto Metropolitan Area. Thus, an integrated and interactive model for alternative urban policies monitoring and simulation is proposed. This simulation involves different dwelling location, economic and professional variables, and their urban and territorial impact to the urban population may be evaluated at once through a proposed cartographic display, developed in Geographic Information Systems.It stands on a professional and geographical stratification of immigrants and ethnic minorities, considering their dwelling and job location and features, as well as their professional characteristics, and uses a large amount of data obtained from the Portuguese Statistical National Institute (Instituto Nacional da Estatística Portugal).The model developed allows the identification of some important dimensions that explain ethnic clusters formation in residential areas and in businesses districts in these metropolitan areas. Besides, it helps to explain how Territorial and Urban Planning (for different planning levels and implementation processes) support a sustained territorial and urban integration of immigrant people and ethnic minorities.